Turning Prospects Into Superstars: The Department Chair’s Role in Mentoring Junior Faculty. - Christian K Hansen (Academic Chairpersons Conference Proceedings, 2017)
Department chairs play a major role in helping new faculty members succeed and become valued and productive member of the faculty. In smaller department, chairs often mentor junior faculty directly, whereas in larger department the chair sometimes has a role in assigning senior faculty mentors to mentor new faculty. Some have referred to hiring faculty as a million dollar investment, and in reality, more than a million dollars is invested from the time the faculty ad is composed until the hired faculty member enter the ranks as a tenured faculty member. When a hired faculty member is turned down for tenure a lose-lose situation is created and a large portion of this investment is lost. Even when a faculty member leaves the university before earning tenure, there is often a perceived loss on both sides of the relationship. Other workshops have focused on principles for conducting successful faculty searches. While this workshop does not go into details of the hiring process, it is obvious that a successful search is a prerequisite for junior faculty members becoming successful. But hiring the right person does not guarantee success of the faculty member or the department. In the workshop we discuss best practices for mentoring new faculty from hiring towards tenure and promotion. The discussions will be supported by small group discussions involving case studies inspired by real world events. Workshop participants will learn about some of the key factors that help or prevent junior faculty from succeeding in the tenure and promotion process and participants will also have an opportunity to share their own success/failure stories when applicable.
Keywords: Mentoring; faculty retention; promotion; tenure; leadership